2017
DOI: 10.1177/2055102917748461
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and trait emotional intelligence among youth

Abstract: This study explored the relationship between family functioning and trait emotional intelligence among 547 respondents, between the age of 16 and 24 years from Malaysia, Iran, China, Sudan, Somalia, Morocco, the United Kingdom, Germany and the Netherlands. The questionnaires were Family Adaptability and Cohesion Evaluation Scale III and Trait Emotional Intelligence Questionnaire Short Form. Pearson correlation analysis revealed a significant relationship between family functioning and trait emotional intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
14
0
3
Order By: Relevance
“…68 Moreover, family flexibility and cohesion were valuable factors in better emotional intelligence among emerging adults. 69 In other studies, Alavi and colleagues 69 found that higher family functioning correlated with higher emotional intelligence considered as a trait. Therefore, the way individuals regulate their emotions on the basis of their personal experience of family functioning can have a great influence on their wellbeing, 70 personal achievement, and psychosocial functioning.…”
Section: Discussionmentioning
confidence: 94%
“…68 Moreover, family flexibility and cohesion were valuable factors in better emotional intelligence among emerging adults. 69 In other studies, Alavi and colleagues 69 found that higher family functioning correlated with higher emotional intelligence considered as a trait. Therefore, the way individuals regulate their emotions on the basis of their personal experience of family functioning can have a great influence on their wellbeing, 70 personal achievement, and psychosocial functioning.…”
Section: Discussionmentioning
confidence: 94%
“…Davenport et al [15] also observed that close and flexible family relationships were related to a lower perception of stress in African-American adults. In addition, Alavi et al [16] pointed out that higher scores in Adaptability and Cohesion are positively related to higher levels of emotional intelligence in young people.…”
Section: Family Functioningmentioning
confidence: 99%
“…Geng (2018) indicated a positive association between emotional intelligence, gratitude and subjective wellbeing of the undergraduate students. He identified that family is another important factor that stimulates the emotional intelligence trait among youth (Alavi et al, 2017).…”
Section: Empirical Reviewmentioning
confidence: 99%